Propositions for place-based policies in making regional innovation systems: evidence from six high-tech industrial development zones in China - Yan, Simin; Zou, Lin; Growe, Anna; Wang, Qixuan (Cities, 2024)
Place-based policies (PBPs) for innovation have profoundly influenced multi-scalar place-builders to bring supra-regional and intra-regional resources into specific spaces to establish so-called ‘regional innovation systems’. Drawing on worldwide debates on PBPs, particularly the criticism of ‘one-size-fits-all’ approaches and the ‘innovation paradox’ in regional innovation policies, we argue that the impacts of PBPs are not a binary issue; rather, they are a complex configuration rooted in regional contexts or intervened with multi-layered innovation systems. A two-dimensional typology with four PBP propositions - investing, demonstrating, interacting, and integrating - is conceptualised. Furthermore, we take a representative PBP - high-tech industrial development zones in China - as a case study and use fuzzy-set qualitative comparative analysis to examine the conditional configurations in real-world policy making, acknowledging the multifaceted and complex interactions within innovation systems. The results indicate that supra-regional pipelines, such as global investments, interact with or adapt to specific regional contexts when introduced to localities. In certain propositions, national platforms can act as a bridge, channelling external resources to targeted territories, which can realise innovation transformations that are not exclusively rooted in specific regional conditions. This paper has implications for configurational PBP making in lagging regions. Ultimately, we call for further in-depth qualitative research on the relationship between the nature of innovation development and regional context.